2022
DOI: 10.1017/s0030605321000995
|View full text |Cite
|
Sign up to set email alerts
|

Species detection framework using automated recording units: a case study of the Critically Endangered Jerdon's courser

Abstract: With the advent of automated recording units, bioacoustic monitoring has become a popular tool for the collection of long-term data across extensive landscapes. Such methods involve two main components: hardware for audio data acquisition and software for analysis. In the acoustic monitoring of threatened species, a species-specific framework is often essential. Jerdon's courser Rhinoptilus bitorquatus is a Critically Endangered nocturnal bird endemic to a small region of the Eastern Ghats of India, last repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yet rare species may not be included in premade tools. Custom detectors can be developed from limited archival recordings with software like Raven Pro 2.0 (Cornell Lab of Ornithology, Ithaca) (see Arvind et al, 2022) or with few‐ and zero‐shot learning algorithms (Wang et al, 2021), and, for anurans in small‐scale deployments, pulse detection tools may be effective (Lapp et al, 2021).…”
Section: Challenges Of Remote Passive Acoustic Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet rare species may not be included in premade tools. Custom detectors can be developed from limited archival recordings with software like Raven Pro 2.0 (Cornell Lab of Ornithology, Ithaca) (see Arvind et al, 2022) or with few‐ and zero‐shot learning algorithms (Wang et al, 2021), and, for anurans in small‐scale deployments, pulse detection tools may be effective (Lapp et al, 2021).…”
Section: Challenges Of Remote Passive Acoustic Monitoringmentioning
confidence: 99%
“…Despite the challenges of data interpretation, and of even executing passive acoustic surveys in remote areas, any new data they yield may be valuable for endangered or data‐deficient species (e.g., Rojas‐Bracho et al, 2022). Thus, for rare, vocally active species, especially anurans, mammals, and birds, bioacoustics may be a powerful tool for conservation (Table 1) (Arvind et al, 2022; Neilson et al, 2013). The logistical challenges of accessing remote areas apply equally to active and passive surveys, and PAM may enable teams to visit more locations by alleviating the time pressure of conducting surveys exclusively during sometimes brief periods of species activity.…”
Section: Opportunities For Conservation Successesmentioning
confidence: 99%
“…The project's camera [10] is installed on the territory of El Valle de Anton in the Cerro Gaital mountains (Figure 1) in Panama. The feeder is located 12 meters from the house and is filled with food several times every day between 5 am and 7 pm.…”
Section: Test Zonesmentioning
confidence: 99%
“…Previously, a study showed the Forest Owlet call can be heard at a distance of 1 km (Ishtiaq and Rahmani 2004); however, this species has a variety of vocalisations that have yet to be assessed systematically. ARUs have been used to detect several endangered species (Arvind et al 2023), and this is proving to be an efficient tool for the rapid assessment of threatened taxa.…”
Section: Introductionmentioning
confidence: 99%